The Effect Of Training On Innovative Work Behavior Mediated By Employee Engagement And Career Development As A Moderation Variable In Employees Of The Aceh Agriculture and Plantation Service (International Journal of Scientific Research and Management (IJSRM), 2025)
This study investigates the impact of training on innovative work behavior, with employee engagement and career development serving as moderating variables among employees of the Aceh Agriculture and Plantation Service. The population consisted of all employees in this agency, totaling 498 ASN. The sample size for this study was 222 ASN, selected through Proportional Random Sampling. The research model was analyzed using SEM software. The findings revealed that training significantly influences innovative work behavior; it also has a considerable impact on employee engagement. Furthermore, employee engagement plays a significant role in fostering innovative work behavior and partially mediates the relationship between training and innovative work behavior. However, career development was found to have no moderating effect on the relationship between training and innovative work behavior.